Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

Re: If r and s are the roots of the equation x^2+bx+c=0, where b [#permalink]
13 Nov 2012, 07:34

Expert's post

Bunuel wrote:

If r and s are the roots of the equation x^2+bx+c=0, where b and c are constants, is rs<0?

Viete's theorem states that for the roots x_1 and x_2 of a quadratic equation ax^2+bx+c=0:

x_1+x_2=\frac{-b}{a} AND x_1*x_2=\frac{c}{a}.

Thus according to the above rs=\frac{c}{1}=. So, we are basically asked whether c<0.

(1) b<0. Not sufficient. (2) c<0. Directly answers the question. Sufficient.

Answer: B.

Hope it helps.

This question drove me insane because I didn't really catch the meaning and reasoning. First of all is not mentioned in MGAMT guide, neither in the 5th edition (a copy of the 4th edition) of algebra guide, only in Gmatclub math book a found a reference.

Now from Bunuel I read Viete's theorem.........

Indeed also this approach is quite simple

Quote:

If c is positive, then the factors you're looking for are either both positive or else both negative. If b is positive, then the factors are positive If b is negative, then the factors are negative. In either case, you're looking for factors that add to b.

If c is negative, then the factors you're looking for are of alternating signs; that is, one is negative and one is positive. If b is positive, then the larger factor is positive. If b is negative, then the larger factor is negative. In either case, you're looking for factors that are b units apart.

Re: If r and s are the roots of the equation x^2+bx+c=0, where b [#permalink]
14 Nov 2012, 09:41

5

This post received KUDOS

carcass wrote:

Bunuel wrote:

If r and s are the roots of the equation x^2+bx+c=0, where b and c are constants, is rs<0?

Viete's theorem states that for the roots x_1 and x_2 of a quadratic equation ax^2+bx+c=0:

x_1+x_2=\frac{-b}{a} AND x_1*x_2=\frac{c}{a}.

Thus according to the above rs=\frac{c}{1}=. So, we are basically asked whether c<0.

(1) b<0. Not sufficient. (2) c<0. Directly answers the question. Sufficient.

Answer: B.

Hope it helps.

This question drove me insane because I didn't really catch the meaning and reasoning. First of all is not mentioned in MGAMT guide, neither in the 5th edition (a copy of the 4th edition) of algebra guide, only in Gmatclub math book a found a reference.

Now from Bunuel I read Viete's theorem.........

Indeed also this approach is quite simple

Quote:

If c is positive, then the factors you're looking for are either both positive or else both negative. If b is positive, then the factors are positive If b is negative, then the factors are negative. In either case, you're looking for factors that add to b.

If c is negative, then the factors you're looking for are of alternating signs; that is, one is negative and one is positive. If b is positive, then the larger factor is positive. If b is negative, then the larger factor is negative. In either case, you're looking for factors that are b units apart.

Could someone tell me if it is an important, really importante question, or negligible ???

Well it would be good to know this concept that in equation ax^2 +bx+c =0 sum of roots =-b/a , product of roots = c/a

Having said that - On GMAT its always test of your reasoning skill. Even if you dont know this you can get the answer. Lets get back to the question

given is, roots of equation are r and s. Thus the equation can be written as: (x-r)(x-s) =0=> x^2 - (r+s)*x +rs =0

However question says , equation is x^2+bx+c=0

Comparing the quotients, b = -(r+s) C = rs

Now, statement 1: b <0 => r+s >0 but we cant say anything about rs. Not sufficient. statement 2: c<0 => rs <0 , exactly what we are looking for. Sufficient

Re: If r and s are the roots of the equation x^2+bx+c=0, where b [#permalink]
14 Nov 2012, 10:02

Expert's post

Vips0000 wrote:

carcass wrote:

Bunuel wrote:

If r and s are the roots of the equation x^2+bx+c=0, where b and c are constants, is rs<0?

Viete's theorem states that for the roots x_1 and x_2 of a quadratic equation ax^2+bx+c=0:

x_1+x_2=\frac{-b}{a} AND x_1*x_2=\frac{c}{a}.

Thus according to the above rs=\frac{c}{1}=. So, we are basically asked whether c<0.

(1) b<0. Not sufficient. (2) c<0. Directly answers the question. Sufficient.

Answer: B.

Hope it helps.

It's a shortcut. I also agree with you to spot the sense of the meaning of the question only thinking that rs <0 have opposite sign

Good to know eventhough what i said is even faster.

Thanks

This question drove me insane because I didn't really catch the meaning and reasoning. First of all is not mentioned in MGAMT guide, neither in the 5th edition (a copy of the 4th edition) of algebra guide, only in Gmatclub math book a found a reference.

Now from Bunuel I read Viete's theorem.........

Indeed also this approach is quite simple

Quote:

If c is positive, then the factors you're looking for are either both positive or else both negative. If b is positive, then the factors are positive If b is negative, then the factors are negative. In either case, you're looking for factors that add to b.

If c is negative, then the factors you're looking for are of alternating signs; that is, one is negative and one is positive. If b is positive, then the larger factor is positive. If b is negative, then the larger factor is negative. In either case, you're looking for factors that are b units apart.

Could someone tell me if it is an important, really importante question, or negligible ???

Well it would be good to know this concept that in equation ax^2 +bx+c =0 sum of roots =-b/a , product of roots = c/a

Having said that - On GMAT its always test of your reasoning skill. Even if you dont know this you can get the answer. Lets get back to the question

given is, roots of equation are r and s. Thus the equation can be written as: (x-r)(x-s) =0=> x^2 - (r+s)*x +rs =0

However question says , equation is x^2+bx+c=0

Comparing the quotients, b = -(r+s) C = rs

Now, statement 1: b <0 => r+s >0 but we cant say anything about rs. Not sufficient. statement 2: c<0 => rs <0 , exactly what we are looking for. Sufficient

Hence B it is.

Of course I know how to get the roots or the use of the discriminant, but in different source that I have this odd angle of the question is not mentioned. Good to know

Re: If r and s are the roots of the equation x^2 + bx + c = 0 [#permalink]
14 Jan 2013, 20:02

Vips0000 wrote:

Well it would be good to know this concept that in equation ax^2 +bx+c =0 sum of roots =-b/a , product of roots = c/a

Having said that - On GMAT its always test of your reasoning skill. Even if you dont know this you can get the answer. Lets get back to the question

given is, roots of equation are r and s. Thus the equation can be written as: (x-r)(x-s) =0=> x^2 - (r+s)*x +rs =0

However question says , equation is x^2+bx+c=0

Comparing the quotients, b = -(r+s) C = rs

Now, statement 1: b <0 => r+s >0 but we cant say anything about rs. Not sufficient. statement 2: c<0 => rs <0 , exactly what we are looking for. Sufficient

Hence B it is.

In this case you have taken (x - r) (X-s) what would happen if they were both positive (x +r) ( x+s) or even one positive / negative _________________

Re: If r and s are the roots of the equation x^2 + bx + c = 0 [#permalink]
20 Jan 2013, 02:21

3

This post received KUDOS

gtr022001 wrote:

fozzzy wrote:

In this case you have taken (x - r) (X-s) what would happen if they were both positive (x +r) ( x+s) or even one positive / negative

yes im confused about the oe, the og states: (x-r)(x-s) = x^2-(r+s)x+rs = x^2+bx+c, but shouldn't it be (x+r)(x-s) = x^2+(r+s)x+rs = x^2+bx+c?

in this case (r+s)x = bx?

pls help

fozzzy & gtr022001,

We cannot use (x+r)(x-s) = x^2+bx+c =0 it would mean (x + r) = 0 or (x - s) = 0, i.e. x = -r orx = s--which is inconsistent with information given in the problem

Note that "-r" is not given as a root. Problem states "r" as one of the roots (along with s) Hence (x-r)(x-s) = x^2+bx+c =0is appropriate with x = r or x = s as roots.

Both roots r & s can take any values -> 0, -ve or +ve if both r & s are either negative or positive, then rs>0 if one of them is positive and other is negative, then rs<0 if both or either one of them is 0, then rs=0

Now refer to Vips0000's explanation that derives c=rs as Statement(2) gives c<0, then rs<0

Hence statement(2) is sufficient to prove rs<0and answer is choice(B). _________________

Re: If r and s are the roots of the equation x^2 + bx + c = 0 [#permalink]
04 Mar 2014, 01:53

Hello from the GMAT Club BumpBot!

Thanks to another GMAT Club member, I have just discovered this valuable topic, yet it had no discussion for over a year. I am now bumping it up - doing my job. I think you may find it valuable (esp those replies with Kudos).

Want to see all other topics I dig out? Follow me (click follow button on profile). You will receive a summary of all topics I bump in your profile area as well as via email. _________________

Re: If r and s are the roots of the equation x^2+bx+c=0, where b [#permalink]
13 Apr 2014, 09:21

Bunuel wrote:

If r and s are the roots of the equation x^2+bx+c=0, where b and c are constants, is rs<0?

Viete's theorem states that for the roots x_1 and x_2 of a quadratic equation ax^2+bx+c=0:

x_1+x_2=\frac{-b}{a} AND x_1*x_2=\frac{c}{a}.

Thus according to the above rs=\frac{c}{1}=c. So, we are basically asked whether c<0.

(1) b<0. Not sufficient. (2) c<0. Directly answers the question. Sufficient.

Answer: B.

Hope it helps.

I actually solved for the discriminant and it ended up taking 3+ minutes. I don't see Viete's theorem in the MGMAT books so please bare with me. I did a search and it basically states that the sum of the two roots is \frac{-b}{a}, and the product of the two roots is \frac{c}{a}, correct?

So using that explanation, it means that since we are looking for the sign of the products of the roots, we need to find the value of \frac{c}{a} and therefore, \frac{(x_1 * x_2)}{a}. Correct? We aren't given any information about a so how can we assume whether a is positive or negative?

EDIT: Are there similar problems that I can apply this theorem to? Thanks!

Re: If r and s are the roots of the equation x^2+bx+c=0, where b [#permalink]
14 Apr 2014, 01:07

1

This post received KUDOS

Expert's post

russ9 wrote:

Bunuel wrote:

If r and s are the roots of the equation x^2+bx+c=0, where b and c are constants, is rs<0?

Viete's theorem states that for the roots x_1 and x_2 of a quadratic equation ax^2+bx+c=0:

x_1+x_2=\frac{-b}{a} AND x_1*x_2=\frac{c}{a}.

Thus according to the above rs=\frac{c}{1}=c. So, we are basically asked whether c<0.

(1) b<0. Not sufficient. (2) c<0. Directly answers the question. Sufficient.

Answer: B.

Hope it helps.

I actually solved for the discriminant and it ended up taking 3+ minutes. I don't see Viete's theorem in the MGMAT books so please bare with me. I did a search and it basically states that the sum of the two roots is \frac{-b}{a}, and the product of the two roots is \frac{c}{a}, correct?

So using that explanation, it means that since we are looking for the sign of the products of the roots, we need to find the value of \frac{c}{a} and therefore, \frac{(x_1 * x_2)}{a}. Correct? We aren't given any information about a so how can we assume whether a is positive or negative?

EDIT: Are there similar problems that I can apply this theorem to? Thanks!

a there is the coefficient of x^2 (ax^2+bx+c=0), hence for x^2+bx+c=0 it equals to 1 (1*x^2+bx+c=0).